2020
DOI: 10.2147/ott.s254997
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circular RNA Hsa_circ_0004018 Inhibits Wnt/β-Catenin Signaling Pathway by Targeting microRNA-626/DKK3 in Hepatocellular Carcinoma</p>

Abstract: Background and Aim: Dysexpression of circular RNAs has been identified in multiple types of cancer. Hsa_circ_0004018 was reported to be significantly downregulated in hepatocellular carcinoma (HCC) and to display HCC-stage-specific expression features. However, the role of hsa_circ_0004018 in HCC progression remains unclear. Methods: The expression of hsa_circ_0004018 or microRNA-626 (miR-626) was detected in tumor tissues and paired non-tumor tissues from HCC patients, as well as in one normal human liver cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
1
22
1
Order By: Relevance
“…The research predicted that DKK3 is the potential target for gene miR-626. The inactivation of DKK3 will reduce the Wnt/β-catenin signaling and suppressed the spread of tumor in HCC conditions [10]. A similar effect is observed with the gene GSTZ1-1 [11].…”
Section: Murthy and Narsaiahmentioning
confidence: 58%
“…The research predicted that DKK3 is the potential target for gene miR-626. The inactivation of DKK3 will reduce the Wnt/β-catenin signaling and suppressed the spread of tumor in HCC conditions [10]. A similar effect is observed with the gene GSTZ1-1 [11].…”
Section: Murthy and Narsaiahmentioning
confidence: 58%
“…Similarly, Zhang M et al also found that RASSF4 overexpression inhibited the proliferation, invasion, and EMT of osteosarcoma cells through the Wnt/β‐catenin pathway 50 . Zhu P et al reported that the interaction of hsa_circ_0004018 and miR‐626/DKK3 with HCC proliferation and migration and xenograft tumor growth involves the Wnt/β‐catenin signaling pathway 11 . Additionally, aberrations in Wnt/β‐catenin are common during human carcinogenesis, which suggests that Wnt/β‐catenin is a major target for the treatment of cancers, including OSCC 51 .…”
Section: Discussionmentioning
confidence: 94%
“…For instance, Zhu et al proposed that miR-626 promoted proliferation and migration of hepatocellular carcinoma cells. 15 Dong et al suggested that miR-626 was up-regulated and exerted an oncogenic role by targeting EYA4 in bladder cancer cells. 25 Similarly, we found the carcinogenic function of miR-626 in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…14 miR-626 is up-regulated in hepatocellular carcinoma patients and promotes hepatocellular carcinoma cell proliferation and migration. 15 Leukemia inhibitory factor receptor (LIFR), a metastasis suppressor, represses cancer malignance in various cancers, including hepatocellular carcinoma, clear cell renal cell carcinoma and gastric cancer. [16][17][18] Moreover, LIFR can inhibit lung cancer cell invasion and metastasis, and it is mediated via circRNA Cysteine-Rich Transmembrane BMP Regulator 1 (circCRIM1)/miR-182/miR-93 axis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation